Transformación de pet mediante hidrolisis acida y Bacillus subtilis para obtener materiales con capacidad de absorcion de metales pesados como cobre y mercurio. - Jaramillo Sánchez, María Teresa (2012)
Heavy metals present in industrial effluents represent a major environmental problem due to mismanagement in the unloading process toward producing watershed pollution at different scales. To develop methods for the removal of copper and mercury, using waste materials that are produced in large quantities in our country such as from PET plastic bottles for water and soft drinks. In this research we studied the sorption capacity of copper and mercury using PET modified by acid hydrolysis and Bacillus subtilis. Evaluating the pH and optimum sorption time, determining a pH of 6 to copper in the semi degradation by acid hydrolysis and pH 8 for Bacillus subtilis and pH 6 for both the semi degradation mercury by acid hydrolysis to Bacillus subtilis. The greater rate of sorption to copper is between 30 and 120 min for 90 min mercury.